Pressure injury prevention practice in Australian intensive care units: A national cross-sectional survey. Issue 2 (March 2023) - Levido, Annabel; Fulbrook, Paul; Barakat-Johnson, Michelle; Campbell, Jill; Delaney, Lori; Latimer, Sharon; Walker, Rachel M.; Wynne, Rochelle; Doubrovsky, Anna; Coyer, Fiona
Abstract: Introduction: Pressure injury (PI) is an ongoing problem for patients in intensive care units (ICUs). The aim of this study was to explore the nature and extent of PI prevention practices in Australian adult ICUs. Materials and methods: An Australian multicentre, cross-sectional study was conducted via telephone interview using a structured survey instrument comprising six categories: workplace demographics, patient assessment, PI prevention strategies, medical devices, skin hygiene, and other health service strategies. Publicly funded adult ICUs, accredited with the College of Intensive Care Medicine, were surveyed. Data were analysed using descriptive statistics and chi-square tests for independence to explore associations according to geographical location. Results: Of the 75 eligible ICUs, 70 responded (93% response rate). PI was considered problematic in two-thirds (68%) of all ICUs. Common PI prevention strategies included risk assessment and visual skin assessment conducted within at least 6 h of admission (70% and 73%, respectively), a structured repositioning regimen (90%), use of barrier products to protect the skin (94%), sacrum or heel prophylactic multilayered silicone foam dressings (88%), regular PI chart audits (96%), and PI quality improvement projects (90%). PI prevention rounding and safety huddles were used in 37% of ICUs, and 31% undertook PI research. Although most ICUs were supported by a facility-wide skin integrity service, it was more common in metropolitan ICUs than in rural and regional ICUs ( p  < 0.001). Conversely, there was greater involvement of occupational therapists in PI prevention in rural or regional ICUs than in metropolitan ICUs ( p  = 0.026). Discussion and conclusion: This is the first study to provide a comprehensive description of PI prevention practices in Australian ICUs. Findings demonstrate that PI prevention practices, although nuanced in some areas to geographical location, are used in multiple and varied ways across ICUs.